Excellence : The Amitabh Bachchan Way - Kapoor, Virender (New Delhi : Rupa, 2017)
What can Amitabh Bachchan's life teach us in our pursuit of excellence? Everything. Amitabh Bachchan is not just a brilliant actor or the 'Superstar of the Millennium'. He is an institution in himself-not just for acting but everything that makes a person successful in his life. Most of his virtues-like professionalism, determination, a never-say-die attitude-are traits which one can follow to achieve the 'Excellence' everyone aspires for. Four National Film Awards, 15 Filmfare Awards and 41 nominations hold testimony to his excellence. How does he sail through different phases of life-the good, the bad and the ugly, which in his case are the best, the worst and the horrid-unruffled? How did he manage an unpredictable film career along with a failed business venture and then rose like a phoenix, never to look back again? All this requires unwavering determination, willpower, patience and a disposition to take it all in one's stride. In this book, educationist and inspirational guru Virender Kapoor analyses each and every trait of Bachchan that is immensely inspiring. Excellence: The Amitabh Bachchan Way not only reveals Big B's professional 'secrets', it also teaches one how to make the best of what we have!
Includes bibliographical references.
Keywords: Non Fiction; Indian Actor